Strategi Internalisasi Nilai Anti Korupsi Sejak Dini - Nelly Agustina; Ratih Ratih; Diah Artika Diningrum (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Corruption is one of the major challenges affecting social, economic, and national development, making preventive efforts through character education essential from early childhood. Instilling anti-corruption values is not solely the responsibility of educational institutions but also requires active involvement from families and communities as primary environments for children's character development. This study aims to analyze strategies for internalizing anti-corruption values from an early age through a literature review and to identify factors that support their effective implementation. The research employed a qualitative approach using the literature review method. Data were collected from academic books, national and international journal articles, policy documents, and previous studies related to character education, anti-corruption education, early childhood education, and parental involvement. Data were analyzed using content analysis by identifying, comparing, and synthesizing findings from relevant literature. The results indicate that the internalization of anti-corruption values can be effectively implemented through role modeling, habituation, integration of anti-corruption values into learning activities, educational games, storytelling, positive reinforcement, and sustainable collaboration among families, schools, and communities. The core values promoted include honesty, responsibility, discipline, caring, hard work, courage, simplicity, and justice. The success of value internalization is influenced by the consistency of value implementation in daily life, teacher competence, parental involvement, and a supportive educational environment. Therefore, strategies for internalizing anti-corruption values from an early age serve as an effective preventive approach to developing future generations with strong integrity and character